Verifying the Placement of Nasogastric Tubes at an Emergency Center: Comparison of Ultrasound with Chest Radiograph - Çağdaş Yıldırım; Selçuk Coşkun; Şervan Gökhan; Gül Pamukçu Günaydın; Ayhan Özhasenekler; Uğur Özkula (Emergency Medicine International)
The objective of this study was to verify the nasogastric tube position with neck ultrasound and subxiphoid ultrasound, by giving air-water mixture and auscultation and to compare the effectiveness of these methods with chest radiography. This is a single-center, prospective, single-blind study. Patients who were admitted to our emergency department and had an indication of nasogastric tube placement were included. Nasogastric tube localization was verified with neck ultrasound and subxiphoid ultrasound, by giving air-water mixture, auscultation, and direct radiography that was accepted as the ‘gold standard technique’. A total of 49 patients (27 Male, 22 Female) with a mean age of 58.3±22.7 years were included. Sensitivity of neck ultrasound was 91.5%, and positive predictive value was 100%. As for the subxiphoid ultrasound sensitivity was 78.72%. When neck ultrasound + subxiphoid ultrasound and giving water-air mixture were combined sensitivity reached 95.74%. Sensitivity of neck ultrasound + subxiphoid ultrasound + air-water mixture + auscultation was 97.87% and positive predictive value was 100%. In the light of our results, neck and subxiphoid ultrasound seem to be an alternative method for verifying nasogastric tube localization. Combination of the air-water mixture and auscultation with ultrasound improves the sensitivity.